(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Polyherbal formulations are those that incorporate two or more herbs. Ayurveda’s medicineformulation is founded on two principles the use of a single drug and the use of a combination of severaldrugs. Polyherbal formulation is the term used to describe the latter. Although it is difficult to define incontemporary terms, Ayurveda’s idea of polyherbalism is unique. Sarangdhar Samhita (Ayurvedicliterature) emphasises the idea of synergism underlying polyherbal compositions. Single herbformulations are well-established because of the potent phytoconstituents they contain, but they aresometimes present in minute amounts that are inadequate to provide the desired therapeutic benefits incertain patients. According to scientific studies, combining these different-potency plants cantheoretically produce a greater result than using each plant alone or adding up their individual effects.This positive herb-herb interaction results in synergism, which could be a pharmacokinetic or apharmacodynamic type of interaction. The excellent efficacy of polyherbal formulations in treating sucha wide range of ailments explains their widespread acceptance. Polyherbal formulations have a broadtherapeutic range (effective at low doses and safe at high doses), less side effects, eco-friendly, cheaperand easily accessible polyherbal formulations are not always safe. According to the Charaka Samhita,Ayurvedic formulas might cause harm if taken incorrectly. Patients, Ayurvedic practitioners, drug-herbinteractions, clinical reproducibility, toxicity owing to faulty production and illogical prescription ofpolyherbal formulations, as well as legislation and regulations, are all factors that contribute to thedifficulties of polyherbal formulations. Polyherbal formulations are becoming more popular, despite thefact that they have a number of drawbacks.